Effects of prenatal oral l-arginine on birth outcomes: a meta-analysis - Eita Goto (Nature Portfolio, 2021)
Abstract Adverse birth outcomes are associated with elevated mortality and morbidity rates throughout life. This meta-analysis of randomised controlled trials examined whether prenatal oral l-arginine has effects on birth outcomes. A total of 45 overall good quality studies were extracted from 10 finally eligible articles. In comparison to controls, providing oral l-arginine to women with a history of poor pregnancy outcomes significantly reduced risks of intrauterine growth retardation neonates, pre-term birth and respiratory distress syndrome (n = 7, 3 and 3, respectively) and significantly increased birthweight and gestational age (n = 8 and 5, respectively) l-Arginine significantly increased Apgar score in women at high risk of pre-eclampsia or with pre-eclampsia or gestational or mild chronic hypertension in comparison to controls (n = 4). l-Arginine showed no significant effect on any other outcome examined (n = 2). The quality of evidence was at least medium or high. Consequently, oral l-arginine may be at least moderately recommended for women with a history of poor pregnancy outcomes and at high risk of pre-eclampsia or with pre-eclampsia or gestational or mild chronic hypertension. However, further studies are required to provide stronger conclusions, partly due to small study effects.